2008
DOI: 10.1080/15513810802319442
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous B-Cell Lymphoma in a Child

Abstract: Primary cutaneous B-cell lymphoma is a B-cell lymphoma of the skin with no evidence of extracutaneous involvement at the time of diagnosis. In this report, we describe an 8-year-old boy who presented with a firm, alopecic, skin-colored, smooth nodule over the right frontal scalp. Histological examination revealed a mid-to deep-dermal mononuclear lesion. Immunohistochemical staining revealed a B-cell population that was CD10(+), CD5(-), CD21(+), and bcl2(-). This pattern of reactivity is characteristic of prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…249 Armitay-Laish et al 234 reported the occurrence of a spindle cell variant of PCFCL in a 17year-old adolescent girl. Condarco et al 250 reported another case of PCFCL in the scalp of an 8-year-old boy. In the large series (n ¼ 69) of pediatric cutaneous NHL from Gratz, a single case of a PCFCL in a 20year-old individual has been reported.…”
Section: Primary Cutaneous Follicle Center Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…249 Armitay-Laish et al 234 reported the occurrence of a spindle cell variant of PCFCL in a 17year-old adolescent girl. Condarco et al 250 reported another case of PCFCL in the scalp of an 8-year-old boy. In the large series (n ¼ 69) of pediatric cutaneous NHL from Gratz, a single case of a PCFCL in a 20year-old individual has been reported.…”
Section: Primary Cutaneous Follicle Center Lymphomamentioning
confidence: 99%
“…Condarco et al. 250 reported another case of PCFCL in the scalp of an 8-year-old boy. In the large series (n = 69) of pediatric cutaneous NHL from Gratz, a single case of a PCFCL in a 20-year-old individual has been reported.…”
Section: Lymphoproliferative Neoplasmsmentioning
confidence: 99%
“…Condarco et al. reported the only pediatric case with PCFCL, successfully treated with surgical resection …”
Section: Cutaneous Mature B‐cell Lymphomasmentioning
confidence: 99%
“…In the paediatric/adolescent age group, the most common cutaneous lymphomas, as in adults, are primary cutaneous T‐cell lymphomas, mainly juvenile mycosis fungoides . Only 25 cases of PCBCL in patients aged 20 years or younger have been reported, 21 with PCMZL, all of whom were at least 11 years old at diagnosis, and four with PCFCL . The findings of these reports suggested that the presentation and course of PCMZL were similar in adolescents and adults, with excellent prognosis .…”
mentioning
confidence: 99%